The Characteristics of Changes in Brain Neurons Typical of Chronic Ischemic Heart Disease - Sherali o‘g‘li, Hasanov Farrukhjon; Umirzakovna, Mamadiyarova Dilfuza (American Journal of Bioscience and Clinical Integrity, 2025)
This article examines chronic ischemic heart disease (CIHD), which is widespread worldwide and holds significant medical importance. Its primary effects are characterized by an impact not only on the cardiovascular system but also on the brain. Cardiac ischemia leads to a reduction in cerebral blood supply, causing significant changes in the structure and functions of brain neurons. This article is dedicated to studying the changes observed in brain neurons as a result of CIHD.